Keadilan Sosial Feminis: Interupsi terhadap Universalisme, Abstraksi dan Imparsialitas - Abby Boangmanalu (Jurnal Perempuan, 2021)
This paper is a theoretical study of the concept of justice from philosophical theories which tend to exclude feminist perspectives. Since the era of Ancient Greek philosophy, the question of justice has been a core concern of social theory. Justice is a concept at the core of moral and political theory. Furthermore, the understanding of justice is very important because it determines how political, social, and economic practices occur in a society. Accordingly, the discussion of justice must start with concrete problems of injustice. But ironically, injustices due to gender discrimination tend to be omitted from the analyses of mainstream justice theories, even though in a society, sex and gender categories intertwine with one’s status, power, opportunity, and position in their society. This paper emphasizes the principles of interactive universalism to ensure justice is inseparable from the ethics of care. This paper finds that the feminist social justice approach is a proper approach to respond to the current situation.